A comparative study on the efficacy of 10% hypertonic saline and equal volume of 20% mannitol in the treatment of experimentally induced cerebral edema in adult rats - Fang Ming; Jiang Wen-Qiang; Deng Yi-Yu; Wang Qiao-Sheng; Zeng Hong-Ke; Chen Chun-Bo; Jiang Xin (BMC Neuroscience, 2010)
Abstract Background Hypertonic saline and mannitol are commonly used in the treatment of cerebral edema and elevated intracranial pressure (ICP) at present. In this connection, 10% hypertonic saline (HS) alleviates cerebral edema more effectively than the equal volume of 20% mannitol. However, the exact underlying mechanism for this remains obscure. This study aimed to explore the possible mechanism whereby 10% hypertonic saline can ameliorate cerebral edema more effectively than mannitol. Results Adult male Sprague-Dawley (SD) rats were subjected to permanent right-sided middle cerebral artery occlusion (MCAO) and treated with a continuous intravenous infusion of 10% HS, 20% mannitol or D-[1-3H(N)]-mannitol. Brain water content (BWC) as analyzed by wet-to-dry ratios in the ischemic hemisphere of SD rats decreased more significantly after 10% HS treatment compared with 20% mannitol. Concentration of serum Na+ and plasma crystal osmotic pressure of the 10% HS group at 2, 6, 12 and 18 h following permanent MCAO increased significantly when compared with 20% mannitol treated group. Moreover, there was negative correlation between the BWC of the ipsilateral ischemic hemisphere and concentration of serum Na+, plasma crystal osmotic pressure and difference value of concentration of serum Na+ and concentration of brain Na+ in ipsilateral ischemic hemisphere in the 10% HS group at the various time points after MCAO. A remarkable finding was the progressive accumulation of mannitol in the ischemic brain tissue. Conclusions We conclude that 10% HS is more effective in alleviating cerebral edema than the equal volume of 20% mannitol. This is because 10% HS contributes to establish a higher osmotic gradient across BBB and, furthermore, the progressive accumulation of mannitol in the ischemic brain tissue counteracts its therapeutic efficacy on cerebral edema.